Risk factors for CAR T-cell manufacturing failure and patient outcomes in large B-cell lymphoma: a report from the UK National CAR T Panel - Vaishali Dulobdas; Amy A. Kirkwood; Fabio Serpenti; Brijesh Gautama; Aikaterini Panopoulou; Amrith Mathew; Sumantha Gabriel; Ram Malladi; Jessica Pealing; Denise Bonney; Emma Nicholson; Caroline Besley; et al. (Blood Cancer Journal)
Abstract CAR T-cell manufacturing failure (MF) is a situation where the manufacturing process fails to yield a product or results in one which is out-of-specification (OOS). We conducted a multicentre retrospective review of factors contributing to MF and patient outcomes. Of 981 large B-cell lymphoma (LBCL) patients approved for CAR T-cell therapy, 38 (3.87%) had MF. Eleven patients received delayed infusion with a product in-specification (delayed-infused) following 21 remanufacturing attempts. OOS product was infused in 13 (OOS-infused), and 14 were not infused. For comparison, we included 38 LBCL controls without MF; 29 received infusion (controls-infused). Prior bendamustine was the only baseline variable associated with MF risk, largely due to therapy within 6 months; 23.7% MF vs 0% controls (P = 0.0029). Overall survival (OS) and progression-free survival (PFS) were not significantly different for infused patients, with 1-year OS (PFS) of 52.8% (46.2%), 46.8% (24.2%) and 68.4% (41.4%) for OOS-infused, delayed-infused and controls-infused respectively (PFS HR OOS-infused vs controls-infused 1.41, P = 0.40; delayed-infused vs controls-infused 1.64, P = 0.25; and OOS-infused vs delayed-infused 0.86, P = 0.76). CRS, ICANS and cytopenias were not significantly different between cohorts. Outcomes for OOS-infused LBCL patients following MF are encouraging. Remanufacturing led to infusion of a product in-specification in around 50% and may be an option for patients where a suitable OOS product is not available.